Clinicopathological Role of Serum-Derived Hyaluronan-Associated Protein (SHAP)-Hyaluronan Complex in Endometrial Cancer - Hiromitsu Yabushita; Keita Iwasaki; Kouhei Kanyama; Yukihiko Obayashi; Lisheng Zhuo; Naoki Itano; Koji Kimata; Akihiko Wakatsuki (Obstetrics and Gynecology International)
The role of hyaluronan (HA), serum-derived HA-associated protein (SHAP)-HA complex and hyaluronan synthase (HAS) in endometrial carcinomas was investigated. The relationship of metalloproteinase (MMP) and its inhibitor (TIMP) with HA and the SHAP-HA complex was also examined. The expression of HAS1 was related to the depth of myometrial invasion and lymph-vascular space involvement. The serum levels of HA, SHAP-HA complex, MMP-9, and TIMP-1 were increased in related with the depth of myometrial invasion, histological grade and lymph-vascular space involvement. They were also higher in the HAS1-positive group compared to -negative group. The serum concentrations of HA and SHAP-HA complex had a significant correlation with the MMP-9 and TIMP-1. The patients with elevated SHAP-HA complex had the shorter disease-free survival. The multivariate analysis revealed that the SHAP-HA complex was the independent variable for disease-free survival of endometrial cancer patients. In conclusion, the elevation of serum SHAP-HA complex depended on the HAS1 expression and the SHAP-HA complex is a useful marker to predict disease recurrence in endometrial cancer patients. The SHAP-HA complex may promote the lymph-vascular space involvement and the synthesis and activation of MMP-9 and TIMP-1 in the progression of endometrial cancer.